PIP5K2A (rs10828317) polymorphism in patients with alcohol dependence and affective disorders - E. V. Mikhalitskaya; N. M. Vyalova; O. Yu. Fedorenko; O. V. Roshchina; G. G. Simutkin; N. A. Bokhan; S. A. Ivanova (Неврология, нейропсихиатрия, психосоматика, 2021)
Alcohol dependence (AD) and affective disorders (ADs) are serious medical and socio-economic problems of modern society. It is hypothesized that both disorders share a common neurobiological basis. Phosphatidylinositol-4-phosphate-5-kinase type 2 alpha (PIP5K2A) plays an essential role in neuronal phosphoinositide signaling pathways. Nonsynonymous rs10828317 mutation of the PIP5K2A gene leads to conformational changes of the PIP5K2A protein and a decrease in the functional activity of this enzyme. In this study, we assessed the possibility of using the rs10828317 polymorphic variant of the PIP5K2A gene as a marker of AD and ADs.Objective: to study the associations of the PIP5K2A (rs10828317) polymorphism with AD and ADs clinical course.Patients and methods. We enrolled 255 patients with AD and 325 patients with ADs. 126 patients with AD and 71 patients with ADs underwent a comprehensive clinical, clinical-dynamic, psychodiagnostic assessment using a set of clinical scales and tests, including Structured Interview Guide For The Hamilton Depression Rating Scale, Seasonal Affective Disorders Version (SIGH-SAD), Alcohol Use Disorders Identification Test (AUDIT), The Obsessive-Compulsive Drinking Scale for craving in alcohol (OCDS).Results and discussion. PIP5K2A (rs10828317) polymorphism in patients with AD was associated with the OCDS mean score after the inpatient treatment; in patients with ADs - with the severity of atypical depression symptoms assessed by SIGH-SAD at the time of admission.Conclusion. The results of our pilot study indicate the involvement of PIP5K2A (rs10828317) polymorphism in the AD and ADs pathophysiology.